Ethnic Concept in Ancient Indian Pholosophy: Characteristics and Meaning of History - NGAN, NGUYEN NGOC KIM (The journal of contemporary issues in business and government, 2021)
The ancient Indian philosophical doctrines have a very early history, it covers most of the different fields of philosophy such as worldview, human view, epistemology, morality. society; Especially in that is the moral ideology with the problems of the purpose, standards and methods of ethical education which are often resolved in terms of spirituality, religion, with the tendency to "inward" to seek unity. Between the “Self” and “Supreme soul” of an individual entity, in order to lead to the highest moral ideal of liberation is one of the thoughts that play a leading role in ancient Indian philosophy.